HUBUNGAN FILSAFAT DENGAN ILMU PENGETAHUAN DAN RELEVANSINYA DI ERA REVOLUSI INDUSTRI 4.0 DAN SOCIETY 5.0 - Della Amabel Odelia Zebua; Asep Mohamad Noor Noor (Asosiasi Dosen Muda Indonesia, 2023)
Philosophy serves as the foundation or basis of human thinking in the academic world, providing rational grounds for the pursuit and research of knowledge. Both philosophy and science are continuously evolving to address the challenges of the time. They act as bridges between change and progress in the world of science and technology. The current technological advancements, known as the Fourth Industrial Revolution and Society 5.0, have shifted human lifestyles from manual labor to the utilization of sophisticated technologies like the internet, robots, artificial intelligence, and computers. This period is often referred to as a dynamic era, as society faces numerous challenges resulting from the rapid development of science and technology. Present-day society must be proactive in confronting the challenges of the times and capable of analyzing the needs for technology.